2013
DOI: 10.1021/ac303084d
|View full text |Cite
|
Sign up to set email alerts
|

“Turn-On” Fluorescent Sensor for Hg2+ Based on Single-Stranded DNA Functionalized Mn:CdS/ZnS Quantum Dots and Gold Nanoparticles by Time-Gated Mode

Abstract: An ultrasensitive "turn-on" fluorescent sensor was presented for determination of Hg(2+). This method is mainly based on Hg(2+)-induced conformational change of a thymine-rich single-stranded DNA. The water-soluble long-lifetime fluorescence quantum dot (Mn:CdS/ZnS) acted as the fluorophore, which was labeled on a 33-mer thymine-rich single-stranded DNA (strand A). The gold nanoparticles (GNPs) functionalized 10-mer single-stranded DNA (strand B) is selected as the quencher to quench the fluorescence of Mn:CdS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(67 citation statements)
references
References 41 publications
2
65
0
Order By: Relevance
“…For instance, Zhu et al [82] reported an Hg 2+ sensor in the near-infrared region based on MAA-capped InP QDs, in which the fluorescence intensity was enhanced in the presence of Hg 2+ because of the formation of HgS nanoparticles, which acted as electron-hole recombination centers. Huang et al [83] presented a "turn-on" fluorescent sensor for Hg 2+ based on single-stranded DNA functionalized Mn:CdS/ZnS QDs and Au NPs. As shown in Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…For instance, Zhu et al [82] reported an Hg 2+ sensor in the near-infrared region based on MAA-capped InP QDs, in which the fluorescence intensity was enhanced in the presence of Hg 2+ because of the formation of HgS nanoparticles, which acted as electron-hole recombination centers. Huang et al [83] presented a "turn-on" fluorescent sensor for Hg 2+ based on single-stranded DNA functionalized Mn:CdS/ZnS QDs and Au NPs. As shown in Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…The electron transfer also leads to quenching of PL of QDs by the ions bound to T-basis. Huang et al developed a "TURN-ON" fluorescent sensor with high sensitivity and selectivity for the determination of mercuric ions (Hg 2+ ) in the aqueous solution on a single-stranded DNA functionalized Mn:CdS/ZnS quantum dots and gold nanoparticles [34]. The water-soluble Mn:CdS/ZnS QD acting as a flourophore was labeled on thymine (T)-rich ssDNA (strand A) and strand B was functionalized with gold nanoparticles (GNPs) which is being used as a quencher to quench the fluorescence of Mn:CdS/ZnSQD.…”
Section: Cation Sensorsmentioning
confidence: 99%
“…Aptamers are antibody-like nucleic acids (Tang et al, 2011) and synthetic nucleic acid ligands; they are of particular importance in analytical chemistry because of their excellent efficiency and selectivity (Huang et al, 2013;Bini et al, 2007;McCauley et al, 2003). Aptamer-based sensors can be used not only to detect biological macromolecules but also detect metal ions.…”
Section: Introductionmentioning
confidence: 99%